Preclinical evaluation of stable integrin αvβ3-specific (198Au)gold nanoparticles for tumor therapy - Davarci, Güllü; Wängler, Carmen; Eberhardt, Klaus; Tulessin, Margaret; Geppert, Christopher; Schirrmacher, Ralf; Fricker, Gert; Mogler, Carolin; Pretze, Marc; Wängler, Björn (Pharmaceuticals, 2025)
Objectives: This paper reports the preclinical evaluation of stable tumor-specific gold nanoparticles (AuNPs) activated by neutron irradiation as a therapeutic option for the treatment of cancers characterized by high tumor angiogenesis. Methods: A selection of promising AuNPs with high avidity to αvβ3-expressing glioma (U-87 MG) cells (IC50 = 82–104 nM) were chosen with different surface loading of Arg-Gly-Asp (RGD) peptides as tumor targeting vectors for integrin αvβ3, a target which is overexpressed in tissues displaying high tumor angiogenesis. Three different [198Au]AuNPs were evaluated applying three injection methods, intravenous (i.v.), intraperitoneal (i.p.), and intratumoral (i.t.), each in a group of six U-87 MG xenograft–bearing mice (54 female athymic nude mice in total). Their biodistribution and tumor accumulation was assessed by in vivo imaging within 1–7 days after injection and 7 days after injection by ex vivo measurement. Results: The developed [198Au]AuNPs exhibited suboptimal biodistribution by i.v. application (accumulation pattern tail > liver > spleen, no significant tumor accumulation) and by i.p. application (accumulation pattern spleen >> liver > pancreas, slight tumor accumulation of <0.3 %ID/g). However, an acceptable biodistribution by i.t. application was observed (5.5 %ID/g in liver, 4.9 %ID/g in spleen, and 3.0 %ID/g in tumor). Conclusions: Despite the very promising in vitro results, the in vivo evaluation suggests that the [198Au]AuNPs represent a platform for the development of restricted therapeutic strategies.